Direct three-dimensional observation of the microstructure and chemistry of C3S hydration. (October 2016) - Hu, Qinang; Aboustait, Mohammed; Kim, Taehwan; Ley, M. Tyler; Hanan, Jay C.; Bullard, Jeffrey; Winarski, Robert; Rose, Volker
Abstract: Disagreements about the mechanisms of cement hydration remain despite the fact that portland cement has been studied extensively for over 100 years. One reason for this is that direct observation of the change in microstructure and chemistry are challenging for many experimental techniques. This paper presents results from synchrotron nano X-ray tomography and fluorescence imaging. The data show unprecedented direct observations of small collections of C3 S particles before and after different periods of hydration in 15 mmol/L lime solution. X-ray absorption contrast is used to make three dimensional maps of the changes of these materials with time. The chemical compositions of hydration products are then identified with X-ray fluorescence mapping and scanning electron microscopy. These experiments are used to provide insight into the rate and morphology of the microstructure formation.